ChemInform Abstract: High‐Pressure Synthesis of Rhombohedral α‐AgGaO2 via Direct Solid State Reaction. Issue 30 (July 2015) - Akhtar, Meysam; Menon, Madhu; Sunkara, Mahendra; Sumanasekera, Gamini; Durygin, Andriy; Jasinski, Jacek B.
Abstract α‐AgGaO2 is prepared via hot pressing of Ag2O and Ga2O3 (diamond anvil cell, 10 GPa, 600 °C, 2 h).